Theatre Talks: How to Accommodate Hygge in Theatre Experience - Skjoldager-Nielsen, Daria (Nordic Theatre Studies, 2022)
Almost each year, the pop-cultural world is buzzing with a “new” Nordic word that can bring a piece of Nordic life to every home. Lagom, fika, fredagsmys or hygge - they all refer to slowness, break, taking a moment to feel good and happy, being considerate. Those concepts are believed to be a Nordic approach to life - and a very desirable one. When I think of theatre in this context, one Nordic invention comes to my mind: theatre talks, which emerged as an audience reception research method in Sweden. They proved to be an effective audience development practice (even for non-theatregoers) in Australia (Scollen), Denmark (Hansen; Lindelof), and Poland (Rapior) because (among other things) they bring the element of pleasure, community building, and feeling safe into the theatre experience especially for non-attenders. In this article I will focus on looking at theatre as a possible “oasis of deceleration” in the constantly accelerating world, using Hartmut Rosa’s theory of social acceleration. By going through the development of theatre talks, I will demonstrate what theatres can gain from using this method - both in attendance and image. I will deliberate on how theatre can become a metaphorically “hyggelig” place for anybody during times when everybody ought to live faster and faster.